1982
DOI: 10.1099/00221287-128-4-823
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the Mycolic Acids from the Walls of Mycobacterium microti

Abstract: Mycobacterium microti walls contained three types of mycolic acids, very similar to those found in Mycobacterium tuberculosis. An alpha-mycolate with two cyclopropane rings, a methoxymycolate with one cyclopropane ring and a methoxyl group, and a ketomycolate with one cyclopropane ring and a keto group were partially characterized. The mycolates made up 34% (by weight) of the peptidoglycan-arabinogalactan-mycolate wall skeleton. Young exponential phase cultures and organisms harvested from mouse lungs containe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
0

Year Published

1986
1986
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(43 citation statements)
references
References 14 publications
1
42
0
Order By: Relevance
“…Thus changes in the proportion of methoxy-and keto-MA had already been reported during cultivation of Mycobacterium microti [26]. In a second landmark paper, Watanabe et al identified and collated the positions of the functional groups in the meromycolate fragments of the MA, revealing the full complexity of the mixtures present and again showing considerable difference between H37Ra and other M.tuberculosis strains [25].…”
Section: Structural Properties Of Mycolic Acids Of Mycobacterium Specmentioning
confidence: 82%
“…Thus changes in the proportion of methoxy-and keto-MA had already been reported during cultivation of Mycobacterium microti [26]. In a second landmark paper, Watanabe et al identified and collated the positions of the functional groups in the meromycolate fragments of the MA, revealing the full complexity of the mixtures present and again showing considerable difference between H37Ra and other M.tuberculosis strains [25].…”
Section: Structural Properties Of Mycolic Acids Of Mycobacterium Specmentioning
confidence: 82%
“…Little is known about how mycolic acid production is regulated. However, it has been shown that mycolic acid composition ratios vary at different growth phases in vitro, during intracellular growth, and at temperature shifts (2,9,17,31,34). Whether feedback inhibition mechanisms maintain the mycolate composition ratio in the cell wall (alpha to methoxy) in wild-type strains remains to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…However, production by other pathogenic mycobacteria varies. What is striking is that virtually all pathogenic mycobacteria produce ketomycolates and that ketomycolate production is increased in vivo (9). It was recently shown that inhalation exposure of guinea pigs to purified methyl ketomycolates but not methyl methoxymycolates or methyl alpha-mycolates induced pulmonary granulomas (30).…”
Section: Discussionmentioning
confidence: 99%
“…7, step 4), which could be the hydroxymycolate or a precursor. The existence of a common precursor for the keto-and the methoxy-mycolic acids would account for the equilibrium observed between the amounts of these two types of mycolate synthesized during the growth of Mycobacterium microti (Davidson et al, 1982).…”
Section: Discussionmentioning
confidence: 99%